Application of Design Thinking For The Design of Bogor Batik Tilu Sauyunan Motif - Asep Taryana; Sri Ratna Handayani Budhie; Amelia Rizky Savitri; Meira Dewi Arianingrum (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The diversity of batik motif designs is one of the key factors driving public interest in batik. In the batik industry, particularly among Small and Medium Enterprises (SMEs), innovation in creating new batik motifs presents a significant challenge to the sustainability of the business in Indonesia. Therefore, this study focuses on one of the SME batik businesses in Bogor.Purpose: The aim of this study is to explore the mapping process involved in creating the Tilu Sauyunan batik motif, a signature design of Bogor City, at the Handayani Geulis Batik Bogor enterprise.Design/Methodology/Approach: This study employs a qualitative approach using the design thinking method to analyze the problems and solutions in the batik creation process.Findings/Results: The analysis reveals that applying the design thinking method to the creation of the Tilu Sauyunan batik motif successfully establishes a visual identity that encapsulates the cultural essence and identity of Bogor.Conclusion: The design thinking approach demonstrated in this study effectively integrates elements and icons of Bogor into the Tilu Sauyunan batik motif, resulting in an appealing and distinctive visual identity.Originality/Value (State of the Art): Handayani Geulis Batik Bogor is a rapidly growing SME in the Indonesian batik industry. Through the innovative efforts of its owner and support from the Indonesian government, the business has expanded internationally. Positioning the Tilu Sauyunan batik motif as a cultural identity and icon of Bogor has the potential to drive further business growth and recognition. Keywords: bogor batik, design thinking, indonesian batik, local wisdom, visual identity